Interpreting neoliberalism with Foucault and Lacan – fantasy, depression and the entrepreneurial subjectivity - Urosevic, Milan (Sociološki pregled, 2024)
The article is dedicated to the construction of a unique theoretical framework aimed at understanding the phenomenon of neoliberalism. In this regard, we primarily rely on the conceptual framework of the governmentality theory, which originates from the work of Michel Foucault. For a better understanding of how neoliberalism interpellates individuals, we will complement the conceptual framework with Lacanian psychoanalysis. We will demonstrate how such a synthesis allows for overcoming the conceptual gap that exists in the governmentality theory between the rationality of governmental regimes and the subjectivity of individuals. We will apply the theoretical synthesis of the governmentality theory and Lacanian psychoanalysis to understand how the neoliberal regime mobilizes subjects into appropriate forms of action, inducing them to adopt the model of subjectivity that Foucault calls homo economicus. Finally, we will examine the phenomenon of depression and show how our theoretical framework can establish a connection between neoliberalism, neoliberal subjectivity, and depression as a mental disorder.
Keywords: neoliberalism; psychoanalysis; fantasy; governmentality theory; subjectivity